PENGARUH UKURAN PERUSAHAAN PERTUMBUHAN PERUSAHAAN DAN INFORMASI LABA TERHADAP KOEFISIEN RESPON LABA PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BEI TAHUN 2018- 2022 - Wahyuni, Rahmi; Andiansyah, Farma; Malahayati, Rina (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
The aim of this research is to determine whether there is an influence of company size, company growth, and information on the profit response coefficient in food and beverage companies listed on the Indonesian Stock Exchange in 2018-2022. In this research, food and beverage companies are listed on the Indonesian Stock Exchange in 2018-2022. The reason for choosing food and beverage companies as part of this research is because there has not been much research conducted on food and beverage companies and there has been a decline in profits that have occurred since 2018. 2018-2022, and the companies used in this research only consist of twenty-six companies. The results of this research show that company size, company growth, and information simultaneously influence the profit response coefficient in food and beverage companies listed on the Indonesian Stock Exchange in 2018-2022. Partial company size has a significant effect on the profit response coefficient in food and beverage companies listed on the Indonesian Stock Exchange in 2018-2022. Partial company growth does not have a significant effect on the profit response coefficient in food and beverage companies listed on the stock exchange Indonesia Pata in 2018-2022. Partial profit information has a significant effect on the profit response coefficient in food and beverage companies listed on the Indonesia Pata Stock Exchange in 2018-2022.